2017
DOI: 10.7759/cureus.1864
|View full text |Cite
|
Sign up to set email alerts
|

Embryonal Rhabdomyosarcoma of the Cervix: A Rare Disease at an Uncommon Age

Abstract: Embryonal rhabdomyosarcoma (RMS) is a rare type of sarcoma, primarily seen in the pediatric and adolescent population. Three subtypes of embryonal RMS are described, with the botryoid type being the most common. The incidence of this disease in adult females is 0.4% to 1% with the affected age group being patients in the third to fourth decade of life. It is exceedingly rare in patients above 40 years of age. We describe the case of a 48-year-old female, gravida 9 para 5, who presented with abnormal vaginal bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Embryonal rhabdomyosarcoma of the genitourinary tract, though being a fairly common neoplasm in children and adolescents, is not a particularly frequent problem in adults. The sarcoma in adult females constitutes 0.4-1% of all cervical malignancies and is extremely rare in patients in post-menopausal age [13]. To the best of our knowledge, we present the first case of post-menopausal cervix RMS from Poland.…”
Section: Discussionmentioning
confidence: 89%
“…Embryonal rhabdomyosarcoma of the genitourinary tract, though being a fairly common neoplasm in children and adolescents, is not a particularly frequent problem in adults. The sarcoma in adult females constitutes 0.4-1% of all cervical malignancies and is extremely rare in patients in post-menopausal age [13]. To the best of our knowledge, we present the first case of post-menopausal cervix RMS from Poland.…”
Section: Discussionmentioning
confidence: 89%
“…Embryonal rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma occurring in the prepubertal age group [ 1 ]. This mesenchymal tumor arises from immature striated skeletal myocytes and can occur anywhere in the head and neck, lymph nodes, extremities, retroperitoneum, and trunk [ 2 ]. The genitourinary tract is the second most common site involved after the head and neck [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This mesenchymal tumor arises from immature striated skeletal myocytes and can occur anywhere in the head and neck, lymph nodes, extremities, retroperitoneum, and trunk [ 2 ]. The genitourinary tract is the second most common site involved after the head and neck [ 2 ]. Embryonal RMS typically affects the vagina or bladder in infants and the uterus or cervix in women of reproductive age [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-cadherin often functions as a tumor suppressor, inhibiting cancer cell invasion and metastases (11), whereas vimentin is a major constituent of the intermediate filament family of proteins, and its overexpression is associated with tumor growth and invasion and poor prognosis in certain types of cancer (12). Immunohistochemical testing for vimentin is positive in rhabdomyosarcoma (RMS) (13). In a recent study, SGK1 was identified and characterized as a tumor-promoting gene, with its inhibition significantly attenuating in vitro and in vivo EMT and metastases formation in prostate cancer, and its overexpression promoting the invasion and migration of the tumor cells (10).…”
Section: Introductionmentioning
confidence: 99%